2015
DOI: 10.3390/nu7125525
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Healthy Beverage Index in Response to an Intervention Targeting a Reduction in Sugar-Sweetened Beverage Consumption as Compared to an Intervention Targeting Improvements in Physical Activity: Results from the Talking Health Trial

Abstract: The recently developed Healthy Beverage Index (HBI) was designed to evaluate overall beverage intake quality (including total fluid consumption and beverage calories), yet no known intervention studies have assessed longitudinal changes to the HBI. The objective of this investigation was to assess changes in HBI scores in response to a sugar-sweetened beverage (SSB) reduction trial as compared to a physical activity comparison group. Participants were enrolled into a six-month, community-based, controlled beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…The Healthy Beverage Index (HBI) [ 31 ] was designed to overcome that challenge by providing a system for evaluating overall beverage quality and comparing that intake against standards set forth by the Dietary Guidelines for Americans and the Beverage Guidance Panel [ 32 ]. Furthermore, preliminary studies indicate that higher HBI scores are positively associated with cardiovascular health [ 31 , 33 ] and may, therefore, prove a useful tool for evaluating the beneficial impact that changes in beverage consumption patterns might have on health.…”
Section: Introductionmentioning
confidence: 99%
“…The Healthy Beverage Index (HBI) [ 31 ] was designed to overcome that challenge by providing a system for evaluating overall beverage quality and comparing that intake against standards set forth by the Dietary Guidelines for Americans and the Beverage Guidance Panel [ 32 ]. Furthermore, preliminary studies indicate that higher HBI scores are positively associated with cardiovascular health [ 31 , 33 ] and may, therefore, prove a useful tool for evaluating the beneficial impact that changes in beverage consumption patterns might have on health.…”
Section: Introductionmentioning
confidence: 99%
“…While lifestyle and genetic factors largely determine the risk for MetS and stroke, a growing body of evidence suggests that dietary factors, including intake of various beverages, are associated with an increased risk of MetS and stroke [4-6].To date, extensive research has been done on the association between individual beverage consumption, particularly sugar-sweetened beverages (SSBs) and coffee and tea, with MetS and stroke [7-10]. However, few publications have examined the overall quality of daily beverage consumption within a broader context of evaluating all consumed beverages as a pattern [11,12]. Therefore, the healthy beverage index (HBI) has been introduced as a holistic concept to evaluate the quality of overall beverage intake and its association with health-related outcomes in nutritional epidemiological studies [13].Previous studies indicated that beverage consumption is association with cardiovascular, all-cause and causespeci c mortality, coronary heart disease and etc [14-16].…”
mentioning
confidence: 99%
“…Energy-balance behaviours, including diet and physical activity, are behavioural precursors to accelerated weight gain ( 2 ) . In the American diet, sugar-sweetened beverages (SSB) are a main contributor to added sugar consumption, total energy intake ( 3 ) and obesity ( 4 ) . Evidence from observational and experimental studies consistently demonstrates strong associations between SSB consumption and increased risk of weight gain, type 2 diabetes mellitus and metabolic syndrome ( 5 13 ) .…”
mentioning
confidence: 99%